Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Pada Karyawan PT Concord Industry - Crisnandi, Amelia Azhara; Chaerudin, Chaerudin (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine the effect of workload and work stress on the performance of PT CONCORD INDUSTRY employees. This research uses a quantitative approach, data collection techniques use questionnaires, interviews and is supported by secondary data through Multiple Linear Regression Analysis Tests, t Tests and F Tests. The results of this research show that there is a partial influence between Workload on Performance with a calculated t value of 7.031, There is a partial influence of work stress on performance with a calculated t value of 5.678, and also a simultaneous influence of work load and work stress on performance for PT CONCORD INDUSTRY employees with a of determination of 0.489 or 48.9%, which means that together work load and Work stress has an influence coefficient of 48.9% on the performance of PT CONCOCRD INDUSTRY employees while the remaining 51.1% is influenced by other variables outside of the research.